Cover Picture: Prodrugs of Persulfide and Sulfide: Is There a Pharmacological Difference between the Two in the Context of Rapid Exchanges among Various Sulfur Species In Vivo? (Angew. Chem. Int. Ed. 20/2022). Issue 20 (19th April 2022) - Yu, Bingchen; Kang, Ting; Xu, Yuan; Liu, Yiqing; Ma, Yaru; Ke, Bowen
Abstract : A series of sulfur species prodrugs (reactive sulfur species in a capsule) that can release pure hydrogen sulfide (H2 S) and hydrogen persulfide (H2 S2 ) was used by Bowen Ke et al. in their Communication (e202201668) to compare the pharmacological differences between sulfide and persulfide. The H2 S2 prodrug exhibits increased activities and reduced toxicity as compared to the H2 S prodrug in vivo, indicating persulfide might represent a better therapeutic paradigm than H2 S.